Faith, Climate, and Energy Frugality: Unravelling the Nexus in European Perspectives - García-García, Pablo (Studia Ecologiae et Bioethicae, 2024)
This study explores the relationship between religious beliefs, perceptions of climate change, and preferences for energy frugality in Europe using data from the November 2023 European Social Survey across 22 countries. The research reveals a predominant inclination toward median values in addressing climate change, with subtle variations based on levels of religiosity. Lower religiosity tends to be associated with a nuanced attribution of climate change to human activity. There is a complex interplay between religiosity and the perception of personal responsibility in mitigating climate change, indicating some polarisation but an overall increasing sense of accountability. Religious affiliations show distinct attitudes, with Protestants more inclined to attribute climate change to human causes. Roman Catholics are closer to some Protestants, while other Christian denominations exhibit flexibility and common ground with Islam and Judaism. However, it is concluded that demographics and political alignment play a more pivotal role compared to religiosity levels or religious denominations.